Perceptions of learners in selected rural secondary schools towards mental illness : the case of Ga-Dikgale Community, Limpopo Province - Makgato, Lephai Irene (University of Limpopo, 2020)
The growing number of young people in schools presenting with mental illness is increasingly becoming a disconcerting issue locally and globally. This qualitative study sought to explore the perceptions of mental illness by learners drawn from four secondary schools in Ga-Dikgale rural community (Limpopo Province). Twenty-seven learners (males = 14; females = 13) were selected through purposive sampling and requested to participate in the study. Semi-structured individual interviews and focus group discussions (n = 2) were conducted. The following three themes emerged from the data: a) Knowledge of mental illness, its causes and symptoms b) Knowledge on the management and types of interventions needed for mental illness c) Challenges associated with mentally ill people. The themes and sub-themes emerging suggested deep seated Afrocentric cultural perceptions which tended to shape learners’ views and understanding of mental illness. Some paradoxical explanations with regard to mental illness also emerged. Based on the findings of the study, it is recommended that mental health literacy campaigns be conducted in schools
Thesis(M.A.( Psychology)) -- University of Limpopo, 2020
Keywords: Learners; Mental illiness; Community; Secondary school; Children with mental disability -- Education (Secondary); Mental illness -- Social aspects; Mental illiness -- South Africa -- Limpopo Province